Human Nature in Ancient Philosophy and its Influence On Modern Philosophy - Nguyen Thi Thu; Nguyen Van Thanh; Nguyen Minh Hoan (Kalagatos, 2025)
The concept of "human nature" is analyzed from the perspective of classical philosophy, with a focus on the thought of Mencius, a great Confucian philosopher. Mencius believed that human nature is inherently good and has the potential to develop morality through education and training. This view has continued to influence modern philosophical and moral theories, such as existentialism and materialism. Through a comparison of ancient and modern philosophical perspectives, the article clarifies the connection between traditional thought and modern theories, helping to better understand the role of human nature in building today's society and morality.